Sustainability reporting and blockchain technology - Singh, Harjit (Professor of finance); Puri, Neha; Mishra, Nandita (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"This book explores the much talked about but less understood issue of sustainability reporting, in a global context, linking it to the application of blockchain and other emerging technologies. It provides a transnational platform to examine the experiences of investors, researchers, academicians, and policymakers as they confront these concerns across a variety of industries and countries, thus offering best-practice guidance to assess the technological landscape and to model sustainable business initiatives. It offers relevant theoretical frameworks and the latest empirical research findings. Further, it argues that in order to reduce 'carbon footprints' globally, by reporting all their emissions through a single blockchain platform, companies can create a standardized space for data to be collected and tracked reliably, allowing for meaningful measurements. The book benchmarks and analyses sustainability performance with respect to numerous laws, norms, codes, performance standards, and voluntary initiatives. It demonstrates how the organization influences and is influenced by expectations about sustainable development and emphasizes the link between financial and non-financial performance, enabling external stakeholders to understand the organization's true value, along with tangible and intangible assets. It will enable readers to increase their understanding of the potential risks and opportunities and avoid environmental, social, and governance failures. The book provides insight into existing research, practice, and outcomes that could clarify and promote the state of the art on themes such as the drivers for sustainability reporting, Environmental, Social, and Governance goals, the influence of blockchain on sustainability reporting as well as the issues and challenges. The book will be a useful guide for scholars, researchers, students, practitioners, regulators and policymakers alike"--
Keywords: Sustainable development reporting; Blockchains (Databases)